2022
DOI: 10.31004/obsesi.v6i4.2314
|View full text |Cite
|
Sign up to set email alerts
|

Development of Research-Based Modules in Educational Psychology Lectures to Improve Creativity

Abstract: Mahasiswa harus memiliki kreativitas yang tinggi agar dapat memenuhi kebutuhan dunia kerja. Kenyataannya, kreativitas mahasiswa masih rendah dan belum ada produk berupa modul berbasis riset yang dapat meningkatkan kreativitas mahasiswa. Penelitian ini bertujuan untuk mengetahui bagaimana perancangan modul berbasis riset pada mata kuliah psikologi pendidikan untuk meningkatkan kreativitas mahasiswa IAIN Batusangkar yang memenuhi kriteria valid, praktis dan efektif. Penelitian ini menggunakan jenis penelitian da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The integration of coding in the development of learning e-modules carried out by Fitriani et al (2022) also showed that learning coding can solve problems in new ways because games on computers use a visual programming language that will train children's logic and thinking concepts (Nadila, 2021). Learning coding will encourage children's imagination and creativity because, with this coding, they can make a game according to the ideas they have.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of coding in the development of learning e-modules carried out by Fitriani et al (2022) also showed that learning coding can solve problems in new ways because games on computers use a visual programming language that will train children's logic and thinking concepts (Nadila, 2021). Learning coding will encourage children's imagination and creativity because, with this coding, they can make a game according to the ideas they have.…”
Section: Discussionmentioning
confidence: 99%
“…With 360 photos, students can do a room tour of each part of the photo and more. In addition, the data helps students visualize the photo more naturally.Studies have shown that hyper-content modules for early childhood education benefit improving HOTS abilities (Sutama, Astuti, Pramono, et al, 2021), teaching linguistic aspects (Ningsih & Mahyuddin, 2021), increasing creativity (Fitriani et al, 2022), improving computational thinking (Muthmainnah Harahap, 2022). The modules can be a digital learning resource in early childhood education study programs (Sutama, Astuti, & Anisa, 2021).…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Fourth, free online storage capacity. Fifth, searchable (easy to browse) (Cahyo Nugroho & Hendrastomo, 2021;Fitriani et al, 2022). In line with science learning, it supports the process of exploring information regarding the development of natural science products which can be done by accessing information widely in digital form (Ariastika, 2022;Tarjiah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%